Electrostatic Limit of Detection of Nanowire‐Based Sensors. Issue 37 (14th July 2015) - Henning, Alex; Molotskii, Michel; Swaminathan, Nandhini; Vaknin, Yonathan; Godkin, Andrey; Shalev, Gil; Rosenwaks, Yossi
<x xml:space="preserve">Abstract</x> Scanning gate microscopy is used to determine the electrostatic limit of detection (LOD) of a nanowire (NW) based chemical sensor with a precision of sub‐elementary charge. The presented method is validated with an electrostatically formed NW whose active area and shape are tunable by biasing a multiple gate field‐effect transistor (FET). By using the tip of an atomic force microscope (AFM) as a local top gate, the field effect of adsorbed molecules is emulated. The tip induced charge is quantified with an analytical electrostatic model and it is shown that the NW sensor is sensitive to about an elementary charge and that the measurements with the AFM tip are in agreement with sensing of ethanol vapor. This method is applicable to any FET‐based chemical and biological sensor, provides a means to predict the absolute sensor performance limit, and suggests a standardized way to compare LODs and sensitivities of various sensors.